Pelatihan Peningkatan Literasi Digital bagi Guru di SD Negeri Citra Indah Sukamaju - Septina Severina Lumbantobing; Andreas Rian Nugroho; Taat Guswantoro; Marta Laura A. Pane; Randi Wardani Saogo; Dian Kristin N. Manullang (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2025)
The advancement of information and communication technology has not only introduced sophisticated digital devices, but also demanded changes in teaching and learning processes. Integrating technology into education has become essential to meet curriculum demands and keep pace with the dynamic developments of the times. Therefore, teachers need to possess adequate digital literacy, including the ability to utilize interactive e-modules through applications such as flipbooks. Flipbooks enable the integration of text, animation, video, and audio, allowing students not only to read but also to interact directly with digital learning materials. This Community Service (PkM) activity was conducted over two days and participated in by 36 teachers. The training results showed an 81% improvement in teachers’ digital literacy skills, based on pretest and posttest comparisons covering indicators such as digital access, understanding, creative production skills, and attitudes toward digital impact. The training received highly positive responses: the material was considered relevant and supportive of teacher creativity (93.9%), the combination of theory and practice was deemed effective (88.9%), the resource persons were rated as competent and communicative (93%), and the supporting facilities were evaluated as adequate (91.6%). Overall, the training received a positive response of 92%, indicating that the activity successfully enhanced teachers' digital competence, creativity, and confidence in developing engaging and interactive flipbook-based learning media